Design of Hydrological Telemetry System Based on NB-IoT Communication Technology - ZHANG Xinmeng; LIU Shuyang; WANG Canhui (Renmin Zhujiang)
With the progress in society and information technology, the rapid emergency response capability for urban flood,drought,and wind prevention needs to be improved.Given the demand, this paper adopts the low-power Internet of Things (NB-IoT) communication technology to design water and rain telemetry terminals in the way of product integration instead of traditional system integration.This technology further reduces the dependence of the equipment on the external environment and improves the stability and reliability of the front-end data acquisition of the hydrological telemetry system,making it possible to deploy the hydrological telemetry terminal for monitoring on a large scale.According to urban emergency prevention and control requirements,Guangzhou Nansha District Flood and Drought Prevention Headquarters Office constructed a new generation of hydrological telemetry system with low cost,strong scalability,and high reliability.By quickly covering urban flood risk points,the system can master real-time water and rain data in the key position of Nansha District to assist the emergency decision,improve emergency response capabilities,and realize the precise distribution of flood control forces,thus reducing the property losses for urban residents.The results show that the hydrological telemetry system based on NB-IoT communication technology applied on a large scale for the first time in Guangzhou can provide efficient data support for dealing with various disasters in flood seasons.